PENERAPAN UI/UX DENGAN METODE DESIGN THINKING PADA VISA (VISITOR SYSTEM APPLICATION) PADA PT DAYAMITRA TELEKOMUNIKASI TBK REGIONAL SUMBAGSEL - Adisty Kharisma Virgiawan; Evi Fadilah (CV. Denasya Smart Publisher, 2024)
Daily activities at PT Dayamitra Telekomunikasi Tbk Regional Sumbagsel involve a lot of interaction with guests. This includes visits from interested parties who come to discuss the project, customer service, or tenant land issues. To manage guest visits more effectively, an organized system is needed. Without a structured system, the process of recording visitor data is carried out manually which can cause inefficiencies, errors in recording data, and difficulties in tracking and accessing visitor information. This research uses the design thought method because its approach focuses on the user (user-centered). To overcome this problem, this report designs a web-based Visitor System Application (VISA). This application is expected to replace manual methods in recording guest data, increasing efficiency, speed and accuracy in data management. The design of the Visitor System Application (VISA) application uses the Design Thinking method with use case diagrams and activity diagrams as a model for creating system prototypes. By implementing this application, it is hoped that PT Dayamitra Telekomunikasi Tbk Regional Sumbagsel can increase productivity and provide convenience in carrying out its work activities, especially in terms of collecting and reporting guest data.